An Analysis of Students’ Obstacles in Reading Comprehension Using Google Classroom for Twelfth Social 2 at SMA Negeri 1 Kota Jambi - Ismiyati, Yanti; Aisyah, Siti; Bafadhal, Utami Aulia (JELT: Journal of English Language Teaching, 2024)
The objective of this research is to identify the obstacles in reading comprehension faced by the twelfth-grade students at SMA Negeri 1 Kota Jambi, to identify the obstacles using Google Classroom faced by the twelfth-grade students at SMA Negeri 1 Kota Jambi. This research is categorized as a quantitative research design. The subject of research was the twelfth-grade students at SMA Negeri 1 Kota Jambi. The technique of collecting the data is a Reading test. The researcher uses the techniques of analyzing the data are data reduction, data display, and conclusion drawing/verification. The researcher presents the data from the obstacles in comprehending English text. The result of the researcher shows that there are 21,9% students who have obstacles in understanding to look for the main idea of the text with the total of incorrect is 47. Then, there are 20% students who have obstacles in understanding the vocabulary of the text with the total of incorrect is 43. Then, there are 20,4% students who have obstacles in understanding and making inference of the text with the total of incorrect is 44. Next, there are 37,7% students who have obstacles in understanding to look detail information of the text with the total incorrect is 81.Keywords: Students’ obstacles, reading comprehension, google classroom